In vitro evaluation of paddy straw based complete feed pellets as livestock feed - BAKSHI, M P S; WADHWA, M (The Indian Journal of Animal Sciences, 2023)
This study was taken up to find out if paddy straw (PS) based complete feed pellets (CFPs) could be prepared by using guar gum as a binder in place of molasses and to assess in vitro nutritional worth as livestock feed. The 8 mm CFPs contained roughage to concentrate ratio of 55:45. The roughage portion was made up of PS and alfalfa hay. With the increase in PS level from 15 to 30%, the level of alfalfa hay was reduced from 40 to 25%. The CFPs were prepared successfully and contained 14.35 to 17.4% CP and 2.99 to 3.31% EE. The bulk density varied between 580.28 to 603.57 kg/m3. With the increase in PS in the CFPs, the NDF and cellulose content increased and CP content decreased linearly. The NGP, true OM digestibility and partitioning factor were not affected by the level of PS in the CFPs. The NDF digestibility increased, while ammonia production and ME availability decreased with the increase in PS level in CFPs. The total and individual VFAs concentration decreased with the increase in PS in CFPs. The relative proportion of propionate and that of isovalerate were improved with the increase in PS in CFPs. The efficiency of rumen fermentation, efficiency of conversion of fermented hexose energy to VFA energy and efficiency of conversion of fermented hexose energy to methane energy declined with the increase in the level of PS in CFPs, resulting in depressed microbial biomass production. It was concluded that CFPs containing graded levels of PS can be developed successfully. However,the efficiency of nutrient utilization, VFA production and microbial biomass production declined at higher levels of PS in CFPs.